Effects of soil components and solution inorganic cations on interactions of imidazolium-based ionic liquid with soils. (1st October 2018) - Miao, Qiuci; Bi, Erping
Abstract: Effects of alkyl chain length of ionic liquid (IL), soil components and solution inorganic cations on a selected IL (1-methyl-3-octylimidazolium chloride, [OMIM]Cl) interaction with Chinese soils were investigated using batch sorption experiments. The results indicated that sorption energy was mainly controlled by chain length of [OMIM]Cl and contents of soil organic matter (SOM). [OMIM]Cl sorption on soils was mainly controlled by cation exchange process. Contributions of SOM and clay minerals (CMs) to [OMIM]Cl sorption were 7.3%–53.8% and 46.2%–92.7%, respectively. SOM possessed higher energy cation-exchange binding sites than CMs. To predict the sorption of [OMIM]Cl on soils, a model for the relationship between sorption coefficient (Kd ) and cation exchange capacity (CEC) from soil components (SOM and CMs, i.e., CECSOM and CECCMs ) as well as solution concentration (Ce ) was established: LogKd  = Log(1.67*CECSOM  + 3.22*CECCMs ) - 0.58LogCe . This model could provide a good prediction for sorption coefficients and the prediction errors were within 0.48 log unit. Competitive effects caused by inorganic cations followed the order of Ca 2+ = Mg 2+  > K +  > Na + . Concentrations and valence of coexisting ions both affect their competitive capability on [OMIM]Cl sorption. The finding of this study provided valuable information for evaluating the fate of [OMIM]Cl in soils. Graphical abstract: Highlights: Sorption energy was mainly controlled by chain length of ILs and contents of SOM. Contributions of SOM and clay minerals to sorption were quantified. A prediction model for [OMIM]Cl sorption on soils was established. SOM possessed higher energy sites for cation-exchange binding than CMs. Valence of inorganic cations led to stronger competition effect than hydrated radii.